AN INTELLECTUAL AND LITERARY REVIEW OF 10th CENTURY A.D. - A Khoso; khairun Nisa (دی اسکالر)
The foreign invaders have come to occupy Sindh always time to time. There is no instance in the history that any one belonging to Sindh soil has invaded on any country of the world. Many religions and cultures erupted on the other soil, and flourished on the soil of Sindh. The people of this soil have shown their hospitality, generously and respects for all the human being but in return they have got atrocity, brutality and unkind response from these foreign invaders. The people of Sindh have got their Sufi nature. The 10th century of Hijra was the country of foreign invaders who occupied Sindh made the Sindh in the chains of slavery and detritus. The mind, thoughts, education, culture and history of Sindh. The 10th year of Hijra proved be the worse. And full of ups and downs of the history of Sindh.